(untitled) (Veterinária Notícias, 2017)
The morpho-functional nature of the plasma membrane assists the transport of nutrients to the interior of spermatozoa, and this requires the physical integrity of the membrane. The aim of the present study was to compare three different dyes used to determine the integrity of the plasma membrane of bovine spermatozoa after freezing. The dyes tested were eosin 3% (p/v), trypan blue 0.4%(p/v), and propidium iodide (1.5 mM). The research employed two sample groups. In the first group, an ejaculate was collected from 11 animals, and in the second group, ten ejaculates were obtained from one animal. The fresh semen was evaluated using microscopy. The post-freezing samples were assessed using microscopy and flow cytometry. The results are presented in the form of average viability percentages ± standard deviations. The values obtained for Groups 1 and 2 using the dyes eosin, trypan blue, and propidium iodide were 64.1±10.1%, 65.6±11.3%, and 64.7±11.1% (Group 1), and 52.1±5.4%, 54.2±6.3%, and 64.1±7.0% (Group 2), respectively. There were no significant differences between the groups (p≥0.001). In comparative analysis of the techniques, flow cytometry enabled a greater number of cell evaluations, compared to phase contrast microscopy, with less variability and faster sample evaluation, hence adding value to the microscopy tests.